2015
DOI: 10.1021/acs.inorgchem.5b01396
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Cd–Zn Sulfide Photocatalysts from Insoluble Hydroxide Precursors

Abstract: The formation of Cd-Zn sulfide solid solutions from mixed hydroxides under hydrothermal conditions is investigated in detail. The work specifically aims to understand the formation and the role of nanotwinned mixed sulfide particles that have been reported to show excellent performance in photocatalytic water splitting (Liu, M.; et al. Energy Environ. Sci. 2011, 4, 1372). The influence of additives, pH, autoclave tumbling, and the state of the mixed hydroxide precursor on the mixed sulfides was studied by XRD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This structure not only ameliorates shortcomings on the stability of metal sulfides, but also greatly promotes photogenerated charge separation, which promotes the photocatalytic activity remarkably. 15,16 In our previous studies, it was observed that T-Zn x Cd 1−x S exhibits excellent reduction ability of hydrogen protons. The apparent quantum yield (AQY) for photocatalytic H 2 evolution can reach up to 62% at 425 nm without any co-catalysts.…”
Section: Introductionmentioning
confidence: 96%
“…This structure not only ameliorates shortcomings on the stability of metal sulfides, but also greatly promotes photogenerated charge separation, which promotes the photocatalytic activity remarkably. 15,16 In our previous studies, it was observed that T-Zn x Cd 1−x S exhibits excellent reduction ability of hydrogen protons. The apparent quantum yield (AQY) for photocatalytic H 2 evolution can reach up to 62% at 425 nm without any co-catalysts.…”
Section: Introductionmentioning
confidence: 96%
“…Previous work has reported that the apparent quantum yield (AQY) for photocatalytic H 2 evolution can reach to 62 % at 425 nm without the presence of any co-catalysts. [17] Therefore, we use Zn x Cd 1À x S with nano-twin crystal structure as catalyst for the photocatalytic reduction of DNDPE to ODA in water-ethanol solution under normal pressure, room temperature and visible light irradiation. Without any noble metal cocatalysts or additional hydrogen source, DNDPE shows the conversion of more than 95 % in 10 min and complete conversion within 40 min, which greatly exceeds traditional catalysis method.…”
Section: Introductionmentioning
confidence: 99%